Memória coletiva de culturas do Nordeste - Domingos Sávio de Almeida Cordeiro (Ciências Sociais Unisinos)
Considering Juazeiro do Norte, in the state of Ceará, as a field of empirical approach, this study is based on the notion that in order to know an area in a social, cultural, and geographical sense, it is necessary to know the experiences of its people. The article discusses the social memories of the Northeast from narrators of Padre Cicero. We present here some reflections beaconed in the capture of oral narratives in which residents identify symbolic contents of the city, its founder, the transmission and exchange of experiences, and we propose an outlook that it is essential to give place to the voices on the myths of social origin formation, because there are in them senses that echo in the subsistence of the symbolic order and provide references to local social groups.